Origins of industrialization in Biscay. Approximation to the liberal legal framework, 1868-1900 - Monge Juarez, Mariano (2021)
In the period from 1868 to 1876, after the approval of the Constitution, a complex process of political and legislative construction of the liberal State took place in Spain, which represented the definitive disappearance of the "Ancien Régime", the advent of capitalist society, and above all, the transformation of Spanish and Biscay society. This new formal context facilitates the development and consolidation of the Industrial Revolution in Biscay (Basque Country, Spain) during the last three decades of the nineteenth century. This article interprets this change in the mode of production from a legal perspective and seeks a first analysis of the emergence of the new Biscay bourgeoisie within the system of client networks proposed by the Monarchist Restoration.